Sociocultural Aspects of Drinking Ciu in Surakarta - Yusana Sasanti Dadtun; Warto Warto; Susanto Susanto; Titis Srimuda Pitana (International Journal of Science and Applied Science: Conference Series, 2022)
The presence of ciu is an important part of the Surakarta society's tradition. Drinking ciu serves a multifaceted symbolic function for their supporting community. the drinking habit of ciu has become a part of the drinking community's daily life, as passed down from their predecessors. The objective of this study was to discover the sociocultural aspects of ciu drinking in Surakarta's ciu drinking community. This study was designed with a qualitative method, which emphasizes the depth of information by delving into the meaning behind the symptoms. In-depth interviews were conducted with ciu drinkers, the community, producers, and government officials. The chairman and staff of Surakarta Kasunanan Palace's Traditional Council Institute (LDA), the abdi dalem, and various parties involved. Archives, newspapers, various reference books, and journal articles that discuss objects related to the research were used as written sources. The study's conclusion is drinking ciu from a review of social aspects pertaining to the existence of three groups of ciu drinkers spread throughout Surakarta, namely the Pangunci Community within the Surakarta Kasunanan Palace, the Pangunci Community outside the Surakarta Kasunanan Palace, and the Ciu drinkers outside the Pangunci Community. Drinking ciu has a special meaning, namely it is a symbol of collective identity, as it is part of the social solidarity of fellow connoisseurs in channeling the burdens of life. The various functions of ciu for the people of Surakarta are closely related to a review of the cultural aspects of drinking ciu. Apart from being passed down from generation to generation, the requirements of traditional rituals, parts of herbs to keep the body's stamina, and parts of traditional medicine ingredients are an important part of ciu's function in Surakarta's culture. Therefore, this study helps the community understand the socio-cultural phenomenon of the ciu drinking tradition in Surakarta, and it helps the government determine policies related to the ciu production system and its distribution.